Exploring the dimensions of place branding: an application of the ICON model to the branding of Toronto. Issue 1 (6th March 2017) - Warren, Giannina; Dinnie, Keith
Abstract : Purpose: The purpose of this paper is to explore the place branding dimensions of a city undergoing a concerted effort to build a distinctive brand for itself. Design/methodology/approach: A qualitative, exploratory approach is adopted, applying the ICON model of place branding to the multistakeholder city branding strategy of Toronto. A combination of interviews, participant observation, content analysis and professional reflection inform the study. Findings: Toronto's emergence as a creative city with global standing has been achieved, in part, through a holistic and collaborative approach that is integrated, contextualized, organic and new. Practical implications: Place and destination promoters are offered a practical application of the ICON model of place branding, informing future initiatives and offering insight into good practice. Originality/value: Viewed through the lens of the ICON model, the paper provides insights into the collaborative and innovate practices that characterize effective city branding.